PENYULUHAN TENTANG PROGRAM CATIN SEBAGAI UPAYA PENINGKATAN KUNJUNGAN CALON PENGANTIN DALAM MENGIKUTI PROGRAM CATIN DI PUSKESMAS TAHTUL YAMAN KOTA JAMBI - Rini, Willia Novita Eka; Pratiwi, Hana (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2024)
ABSTRACTOne of the efforts to improve health status, especially in reproductive health, is to carry out examinations of prospective brides and grooms (catin). CATIN examinations are carried out in the form of catin classes. CATIN classes are held and also provide pre-marital counseling and physical examinations for prospective brides and grooms with the aim of helping individuals prepare to be able to live a married life and be able to create a harmonious family. The aim of this activity is to increase the knowledge of prospective brides and grooms about the importance of carrying out health checks and taking courses for prospective brides and grooms so as to increase the number of visits by prospective brides and grooms to take part in the CATIN program at the Tahtul Yaman Health Center. This activity was carried out using several methods, namely first, the approach method with stakeholders and the community, especially young people in the working area of the Tahtul Yaman Community Health Center, second, the partner participation method, third, implementing outreach activities, as well as monitoring and evaluating activities. The counseling activity at the Tahtul Yaman Community Health Center went well and was welcomed enthusiastically by the participants. The activity was also accompanied by the display of posters at the Community Health Center, as well as in several places frequently visited by the public. With the outreach activities and posting of leaflets about the CATIN program, it is hoped that participants will increase their knowledge and that participants will be able to apply and disseminate the information that has been given to couples who are getting married. From this activity it can be concluded that there is a positive contribution in improving the level of public health at the Tahtul Yaman Community Health Center, Jambi City.Keywords: Program Catin, Health Check, Knowledge ABSTRAKSalah satu upaya untuk meningkatkan derajat kesehatan, terutama dalam kesehatan reproduksi salah satunya adalah melaksanakan pemeriksaan calon pengantin (catin). Pemeriksaan catin dilaksanakan dalam bentuk kelas catin. Kelas catin dilangsungkan juga memberikan konseling pranikah dan pemeriksaan fisik bagi calon pengantin dengan tujuan untuk membantu kesiapan individu untuk mampu menjalani kehidupan berumah tangga dan mampu menimbulkan keluarga yang harmonis. Tujuan dari kegiatan ini ialah diharapkan menambah pengetahuan calon pengantin tentang pentingnya melakukan pemeriksaan kesehatan dan mengikuti kursus calon pengantin sehingga meningkatnya angka kunjungan calon pengantin untuk mengikuti program CATIN di Puseksmas Tahtul Yaman. Kegiatan ini dilakukan dengan beberapa metode yaitu yang pertama metode pendekatan dengan steakholder dan masyarakat terutama pemuda pemudi di wilayah kerja Puskesmas Tahtul Yaman, kedua, metode partisipasi mitra, ketiga pelaksanaan kegiatan penyuluhan, serta melakukan monitoring dan evaluasi kegiatan. Kegiatan penyuluhan di Puskesmas Tahtul Yaman berjalan dengan baik dan disambut antusias oleh peserta. Kegiatan juga disertai dengan penempelan poster di Puskesmas, juga di beberapa tempat yang sering dikunjungi masyarakat. Dengan adanya kegiatan penyuluhan dan penempelan leaflet tentang program CATIN ini diharapkan menambah pengetahuan bagi para peserta dan peserta bisa menerapkan serta menyebarkan informasi yang telah diberikan kepada pasangan yang akan melangsungkan pernikahan. Dari kegiatan ini dapat disimpulkan bahwa terdapat kontribusi yang positif dalam rangka peningkatan derajat kesehatan masyarakat di Puskesmas Tahtul Yaman Kota Jambi.Kata kunci: Program Catin, Pemeriksaan Kesehatan, Pengetahuan